2014
DOI: 10.4049/jimmunol.1203516
|View full text |Cite
|
Sign up to set email alerts
|

“Activated” STAT Proteins: A Paradoxical Consequence of Inhibited JAK-STAT Signaling in Cytomegalovirus-Infected Cells

Abstract: We have previously characterized mouse CMV (MCMV)–encoded immune-evasive IFN signaling inhibition and identified the viral protein pM27 as inducer of proteasomal degradation of STAT2. Extending our analysis to STAT1 and STAT3, we found that MCMV infection neither destabilizes STAT1 protein nor prevents STAT1 tyrosine Y701 phosphorylation, nuclear translocation, or the capability to bind γ-activated sequence DNA-enhancer elements. Unexpectedly, the analysis of STAT3 revealed an induction of STAT3 Y705 phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 75 publications
2
26
0
Order By: Relevance
“…For VZV, STAT3-activated survivin was found to be involved in proreplication activity, reflecting the prosurvival activities of STAT3 via survivin reported for PEL cells (24). However, human cytomegalovirus blocks STAT3 phosphorylation, though it requires it for optimal replication, and mouse cytomegalovirus induces phosphorylation of STAT3 but not STAT3-responsive cellular genes, suggesting novel, virus-redirected activities of the transcription factor (37,38). Our findings of vIL-6/gp130 and STAT3 involvement in HHV-8 productive replication could facilitate the development of therapeutic interventions for the treatment of HHV-8-associated diseases, to which productive replication contributes significantly.…”
Section: Contribution Of Stat3 To Hhv-8 Replicationmentioning
confidence: 79%
“…For VZV, STAT3-activated survivin was found to be involved in proreplication activity, reflecting the prosurvival activities of STAT3 via survivin reported for PEL cells (24). However, human cytomegalovirus blocks STAT3 phosphorylation, though it requires it for optimal replication, and mouse cytomegalovirus induces phosphorylation of STAT3 but not STAT3-responsive cellular genes, suggesting novel, virus-redirected activities of the transcription factor (37,38). Our findings of vIL-6/gp130 and STAT3 involvement in HHV-8 productive replication could facilitate the development of therapeutic interventions for the treatment of HHV-8-associated diseases, to which productive replication contributes significantly.…”
Section: Contribution Of Stat3 To Hhv-8 Replicationmentioning
confidence: 79%
“…Indeed, negative feedback is well established in STAT3 signaling and can exist at many levels. In our mouse models, we may be observing the consequences of negative-feedback inhibition when tonic Stat3 hyperactivation exceeds a threshold, as previously observed (34)(35)(36). Furthermore, STAT3 signaling pathways are subject to significant crosstalk.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, MCMV provides a unique opportunity to study mechanisms that affect the host-pathogen balance. Previous studies showed that MCMV suppressed IFNAR signaling of MCMV-permissive fibroblasts (19,39). Furthermore, other MCMV genes may reduce the induction of IFN-I responses in fibroblasts (21).…”
Section: Discussionmentioning
confidence: 96%